Muscle Oxygenation During Hypoxic Exercise in Children and Adults - Ušaj, Anton; Mekjavic, Igor B.; Kapus, Jernej; McDonnell, Adam C.; Jaki Mekjavic, Polona; Debevec, Tadej (Frontiers in Physiology, 2019)
Introduction: While hypoxia is known to decrease peak oxygen uptake (V ̇o2 max) and maximal power output in both adults and children its influence on submaximal exercise cardiorespiratory and, especially, muscle oxygenation responses remains unclear. Methods: Eight pre-pubertal boys (age=8±2yrs.; body mass (BM)=29±7kg) and seven adult males (age=39±4yrs.; BM=80±8kg) underwent graded exercise tests in both normoxic (PiO2=134 ± 0.4 mmHg) and hypoxic (PiO2=105 ± 0.6 mmHg) condition. Continuous breath-by-breath gas exchange and near infrared spectroscopy measurements, to assess the vastus lateralis oxygenation, were performed during both tests. The gas exchange threshold (GET) and muscle oxygenation thresholds were subsequently determined for both groups in both conditions. Results: In both groups, hypoxia did not significantly alter either GET or the corresponding V ̇o2 at GET. In adults, higher V ̇E levels were observed in hypoxia (45±6 l/min) compared to normoxia (36±6 l/min, p < 0.05) at intensities above GET. In contrast, in children both the hypoxic V ̇E and V ̇o2 responses were significantly greater than those observed in normoxia only at intensities below GET (p < 0.01 for V ̇E and p=<0.05 for V ̇o2). Higher exercise-related heart rate levels in hypoxia, compared to normoxia, were only noted in adults (p < 0.01). Interestingly, hypoxia per se did not influence the muscle oxygenation thresholds during exercise in neither group. However, and in contrast to adults, the children exhibited significantly higher total haemoglobin concentration during hypoxic as compared to normoxic exercise (tHb) at lower exercise intensities (30 and 60 W, p= 0.01). Conclusions: These results suggest that in adults, hypoxia augments exercise ventilation at intensities above GET and might also maintain muscle blood oxygenation via increased heart rate. On the other hand, children exhibit a greater change of muscle blood perfusion, oxygen uptake as well as ventilation at exercise intensities below GET.